Cover Feature: A "Multi‐Heavy‐Atom" Approach toward Biphotonic Photosensitizers with Improved Singlet‐Oxygen Generation Properties (Chem. Eur. J. 38/2019). Issue 38 (5th June 2019) - Galland, Margaux; Le Bahers, Tangui; Banyasz, Akos; Lascoux, Noëlle; Duperray, Alain; Grichine, Alexei; Tripier, Raphaël; Guyot, Yannick; Maynadier, Marie; Nguyen, Christophe; Gary‐Bobo, Magali; Andraud, Chantal; et al.
Abstract : Towards improved lanthanide complexes for two‐photon mediated singlet oxygen production: The very large intersystem crossing efficiency results from the combination and interplay of bromine atom substituents, placed along the π‐conjugated antenna, and a heavy rare‐earth element coordinated to a central TACN ligand. Two‐photon‐activated singlet oxygen generation leads to tumor cell death, which illustrates the potential of this new class of compounds as theragnostic agents. More information can be found in the Full Paper by M. Gary‐Bobo, C. Andraud, C. Monnereau, O. Maury, et al. on page 9026 .